Role of NGOs in Rural Development in Nepalese Context (Researcher CAB: A Journal for Research and Development, 2023)
This research aims to revive dormant NGOs for rural and community development, emphasizing their limited and passive engagement in a specific region, which hinders meeting community needs. It highlights the significance of program selection based on local needs, prioritizing it over donor accessibility as well as that of human resource development within and outside NGOs. Furthermore, the research addresses the issue of the exclusion of marginalized groups due to the dominance of local elites, advocating for empowerment and capacity building. Despite limitations, NGOs are acknowledged as catalysts for transformative change, offering practical insights for revitalizing NGOs and promoting inclusive grassroots development.